Thomas Frederick Tout (1855-1929) Refashioning history for the twentieth century - Barron, Caroline M.; Rosenthal, Joel T. (IHR Conference Series, 2019)
Thomas Frederick Tout (1855-1929) was arguably the most prolific English medieval historian of the early twentieth century. The son of an unsuccessful publican, he was described at his Oxford scholarship exam as 'uncouth and untidy'; however he went on to publish hundreds of books throughout his distinguished career with a legacy that extended well beyond the academy. Tout pioneered the use of archival research, welcomed women into academia and augmented the University of Manchester's growing reputation for pioneering research. This book presents the first full assessment of Tout's life and work, from his early career at Lampeter to his work in Manchester and his wide-ranging service to the study of history. Selected essays take a fresh and critical look at Tout's own historical writing and discuss how his research shaped, and continues to shape, our understanding of the middle ages, particularly the fourteenth century. The book concludes with a personal reflection on Tout by his grandson, Tom Sharp.